Radiological Features of Joubert's Syndrome - Stroscio, Giovanni; Cuppari, Caterina; Ceravolo, Maria Domenica; Salpietro, Annamaria; Battaglia, Francesco; Sallemi, Alessia; Fusco, Monica; Ceravolo, Antonio; Iapadre, Giulia; Calì, Elisa; Impollonia, Daniela; Granata, Francesca (Journal of Pediatric Neurology, 2023)
Joubert syndrome (JS) is a rare autosomal recessive disorder. All patients affected by this syndrome presented a characteristic picture of cranial fossa malformations, called “molar tooth sign.” This sign is defined by the presence in axial section at the level of a deck/midbrain, of hypo/dysplasia of the cerebellar vermis, abnormally deep interpeduncular fossa and horizontalized thickened and elongated superior cerebellar peduncles. Although “molar tooth sign” is peculiar of JS, other radiological findings have been also reported in these patients. Here, the authors briefly assumed the principal magnetic resonance imaging findings of JS.
Keywords: Joubert syndrome; radiological findings; “molar tooth sign”